Optimizing verbal and nonverbal communication in physical education teachers, fitness instructors and sport coaches - Castaner, M.; Miduel, C.; Franco, S.; Rodrigues, J. (Mixed methods research in the movement sciences: Case studies in sport, physical education and dance, 2014)
Case Study 1: Identifying and optimizing nonverbal communicative styles in physical education teachers Case Study 2: Coaches' communication in competitive match situations. Case Study 3: The behaviour of fitness instructors and the preferences and satisfaction levels of users. The case studies described in this chapter refer to research into the communication of teachers, coaches and instructors in the context of physical education and sport. The arm is to illustrate the versatility of verbal and nonverbal communication in these professionals and to examine its importance as regards the teaching or training process. What the studies described have in common is that they all made use of observational methodology. This approach was chosen due to the habitual nature of the behaviour being observed and the fact that the context is a naturalistic one. Furthermore, the Flexibility and rigour of this methodology makes it fully consistent with the characteristics of this kind of research and it has become a standard approach to observational enquiry. The results derived from the observations of physical education teachers, fitness instructors and coaches were combined with those obtained via questionnaires and interviews conducted with them. This enabled us to obtain and combine both QUAN and QUAL data, the aim being to identify and, subsequently, to optimize the communication of these professionals.